Development and Policy-driven to the Ministry of Public Health Goal “Happier Health Care Workers” - คูหา, ธิติภัทร; อิทธิชัยวัฒนา, จิราพร (Journal of Health Science of Thailand, 2021)
The objective of this study was to develop and mobilize the policy to achieve the Ministry of Public Health’s goal on “Happier Health Care Workers” which had been performed since the fiscal year 2017–2020, in order to evaluate effectiveness and to make policy recommendations. It was conducted as a descriptive research using mix method. The study was divided into two parts. The first part was to study the development and policy-driven implementation using documentary research; and the second part was to evaluate effectiveness of the policies on Happinometer, Happy Public Organization Index, bright spot policy-driven organization and opinions for development and policy-driven by using mix methods which included secondary data analysis, focus group and survey research. The results of the study showed that the substantial points of policy development and implementation were the clear policy statements, evidence-based development and regular monitoring. The average Happinometer index in the year 2019 was 63.41, which was at happy level. This value appeared to increase from the year 2017 in almost every dimensions. However there were some dimensions which the average value was still at the lowest level including dimension of happy-money, happy-relax and work-life balance. Moreover, the happy public organizational index was at an average of 55.25, which was in the criteria for ‘increased attention’, but the investment and management components were at the lowest average. The lesson learned from the bright spot agency indicated that the key success factors were the attention of leaders, policy continuity, the change agent support team and also the progressively plan for human development relating to the organization’s goals. The survey on the opinions of personnel responsible for driving the policy revealed high level of agreement, particularly on the topics relevant to the problems and context of the organization, executive support, clear assignment for each personnel and evidence based management. Policy recommendations from this study included (1) setting continuing policy on “Happier Health Care Workers” together with the enhancement of monitoring system and strengthening of teams and network, together with feedback information to the agency, (2) setting role model of leadership, motivating and defining them as one of the criteria for career path of executive, (3) develop and drive policy focus on happy relaxation and work-life balance based on the available information; and to centralize the efficiency of system management along with the organization’s administrators in order to focus on creating happy organization and fairly managing the workload.